A case of Mirizzi syndrome accompanied by a pseudoaneurysm that ruptured into the gallbladder: successfully treated by embolization of aneurysm and sequential surgery - Ryosuke Fukushima; Norihiro Ishii; Norifumi Harimoto; Kenichiro Araki; Akira Watanabe; Mariko Tsukagoshi; Kei Hagiwara; Takahiro Yamanaka; Ken Shirabe (Surgical Case Reports, 2022)
Abstract Background Although visceral aneurysms are relatively rare, it can be life-threatening in case it ruptures. We report a case of Mirizzi syndrome accompanied by a pseudoaneurysm that ruptured into the gallbladder. Case presentation The patient was a 73-year-old woman with persistent gastrointestinal bleeding and progressive jaundice. Examination revealed a pseudoaneurysm in the gallbladder artery or hepatic artery branch, and biliary hemorrhage due to gallbladder perforation was suspected. Urgent abdominal angiography revealed a pseudoaneurysm measuring 50 × 32 mm that had ruptured directly from the right hepatic artery or the cystic artery into the gallbladder. The pseudoaneurysm was successfully coiled and the bleeding was stopped. The presence of ongoing obstruction due to Mirizzi syndrome resulted in an emergency cholecystectomy being performed on the same day. On removing the impacted gallstone from the neck of the gallbladder, we found an obstruction between the lateral wall of the common bile duct and the gallbladder, this condition was diagnosed as Mirizzi syndrome with a biliobiliary fistula. After removing the impacted gallstone, a T-tube was inserted into the common bile duct. Bile leakage was observed postoperatively, but it improved with drainage. The patient fully recovered. Conclusions We present our experience with a case of Mirizzi syndrome accompanied by a ruptured pseudoaneurysm successfully treated with coil embolization followed by cholecystectomy. In this case, the pseudoaneurysm may have been caused by inflammation due to cholecystitis or compression of the arterial wall by a gallstone. To the best of our knowledge, Mirizzi syndrome associated with pseudoaneurysm rupture is rare. Our study suggested that cholecystectomy preceded by transcatheter arterial embolization is an effective strategy to control bleeding in patients with hemobilia due to aneurysm.